Accuracy of dual energy X-ray absorptiometry (DXA) in assessing carcass composition from different pig populations. (November 2016) - Soladoye, O.P.; López Campos, Ó.; Aalhus, J.L.; Gariépy, C.; Shand, P.; Juárez, M.
Abstract: The accuracy of dual energy X-ray absorptiometry (DXA) in assessing carcass composition from pigs with diverse characteristics was examined in the present study. A total of 648 pigs from three different sire breeds, two sexes, two slaughter weights and three different diets were employed. DXA estimations were used to predict the dissected/chemical yield for lean and fat of carcass sides and primal cuts. The accuracy of the predictions was assessed based on coefficient of determination ( R 2 ) and residual standard deviation (RSD). The linear relationships for dissected fat and lean for all the primal cuts and carcass sides were high ( R 2 > 0.94, P < 0.01), with low RSD (< 1.9%). Relationships between DXA and chemical fat and lean of pork bellies were also high ( R 2 > 0.94, P < 0.01), with RSD < 2.9%. These linear relationships remained high over the full range of variation in the pig population, except for sire breed, where the coefficient of determination decreased when carcasses were classified based on this variable.